An Interview with Dr. Lindsay Gibson and Dr. Catherine Duquette: “Exploring Historical Thinking and the Legacy of Dr. Peter Seixas”. A Special Issue of Revista Perspectivas - Gibson, Lindsay (2024)
The interview has been edited by Lindsay Gibson and Catherine Duquette for clarity, brevity, and accuracy. Footnotes have been added to provide links to organizations, websites, articles, books, and resources mentioned in the interview. The interview examines Dr. Peter Seixas’ model of historical thinking, its scope, and its achievements in the subject of Social Studies.